Strength and Microfabric of Expansive Soil Improved with Rice Husk Ash and Lime - Jinrong Ma; Yunhe Su; Yuyi Liu; Xiangling Tao (Advances in Civil Engineering)
Expansive soil has harmful effect on engineering. Rice husk ash (RHA) has high pozzolanic activity, so it can form new cementing material with lime or cement to solidify soil. In this paper, the tests of free expansion rate, water ratio limit, and optimum moisture content (OMC) are carried out; then, RHA and lime were added to artificial soil in different proportions of 5, 10, 15, and 20% by weight, in which the ratio of RHA to lime is 80 : 20. The unconfined compressive strength (UCS) in different curing age is measured, and the improvement effect of RHA and lime to expansive soil can be obtained. Finally, the reason of improvement effect is explained by using the scanning electron microscope (SEM). The results of the study show that (1) for the best utilization effect, the optimum percentage of RHA is 12% and lime is 3%; (2) the UCS is 2.6 times of the pure soil after curing of 14 d under the optimum percentage; (3) the curing age has a significant effect on strength; (4) the main reason for the strength increase of the modified soil is that the crystal produced by the pozzolanic activity fills the pores of the soil.